The influence of maternal islet beta-cell autoantibodies in conjunction with gestational hyperglycemia on neonatal outcomes. - Zhe Li; Tian-mei Wu; Wei-jie Ming; Xin Chen; Xiao-min Xiao (PLoS ONE, 2015)
To determine the predictive value of the presence of maternal islet beta-cell autoantibodies with respect to neonatal outcomes.A total of 311 pregnant women with abnormal 75 g oral glucose tolerance test (OGTT) results were enrolled in this study. Maternal glutamic acid decarboxylase autoantibodies (GADA), islet cell autoantibodies (ICA) and insulin autoantibodies (IAA) were tested in fasting blood both on the day following the routine OGTT and before delivery. The birth weight, Apgar score, blood glucose and outcomes of each neonate were later evaluated and recorded.1. In this study, 33.9% of the pregnant women with gestational hyperglycemia had detectable levels of one or more types of anti-islet cell antibodies in the third trimester. The proportion of women who produced GADA and/or ICA was significantly higher in the group of women with gestational hyperglycemia than in the control group (P<0.05). The groups similarly differed in the proportion of women who tested positive for any anti-islet cell antibody (P<0.05). 2. Of the patients in our study, those who produced GADA exhibited an increase in uterine and umbilical arterial pulsatility indexes (PIs) during the third trimesters compared with the control group (P˂0.05). Additionally, an increased frequency of fetal growth restriction (FGR) was observed in the infants of women who produced IAA during pregnancy compared with those without autoantibodies (P˂0.05). 3. The rate of newborn admission to the neonatal intensive care unit (NICU) was significantly associated with the presence of maternal ICA during the third trimester (OR, 6.36; 95% CI, 1.22-33.26). 4. The incidence of neonatal asphyxia was associated with the presence of maternal GADA in both the second (OR, 10.44; 95% CI, 1.46-74.92) and the third (OR, 8.33; 95% CI, 1.45-47.82) trimesters.Approximately one-third of the women with gestational hyperglycemia produced anti-islet cell antibodies. The incidence of FGR was higher in women with gestational hyperglycemia who produced IAA than in those without autoantibodies. Maternal ICA production in the third trimester was a risk factor for the subsequent admission of newborns to the NICU. Furthermore, the presence of maternal GADA placed the neonate at increased risk for asphyxia.